ИССЛЕДОВАНИЕ НЕКОТОРЫХ ФАКТОРОВ, ВЛИЯЮЩИХ НА ПОЛИТИЧЕСКИЙ ВЫБОР МОЛОДЁЖИ /МОЛОДЫХ ЛЮДЕЙ/ - Дангаасурэнгийн ОДМАА /Доктор Ph.D/ (Politology, 2023)
Mongolians have turned into democratic society for 26 years. It hasn’t paid no regard to Public congress election in 1990, Great national conference was elected 7 times, President election was elected 6 times and local election was elected 7 times. Total 20 times election was hold since 1992 which constitution was approved. But our electors especially youth participation in election was constantly decreased. Therefore, researchers ought to pay attention for it. Researching election process gives chances to discover democratic main criteria of all countries that a political condition, political party formation, people’s political culture and education and activities of media. Consequently, influencing vote of electors seems that just a bit for individual person but if electors don’t participate, a participation level will decrease. Thus, it will be difficult to make people attend and it might be hold an election again. For this reason, government ought to pay attention to increase electors’ political participation. Therefore, this paper was considered to define main factors that influence on youth political selection, how does it influence and how to pay attention for it and work.